Role of pleural biopsy in diagnosis of unilateral pleural effusion:study of 50 cases in Rangpur Medical College & Hospital, Rangpur - Shaheduzzaman, AKM; Sarkar, Devendra Nath; Wahid, Md Ferdous; Alam, Md Shafiul; Rahman, Md Mahfuzer; Haque, Md Ashraful; Sarker, Md Kumruzzaman; Mondal, Ratindra Nath; Bidhu, BD; Shaha, Amaresh Chandra; Alam, Md Mobasher; Hossain, Md Zakir; et al. (Bangladesh Journal of Medicine, 2016)
Background: Pleural effusion remains the most common manifestation of pleural pathology. Sometime it is difficult to differentiate between tuberculous and malignant pleural effusion on routine cytological and biochemical examination. So pleural biopsy is an important tool for evaluating undiagnosed pleural effusion. Aim: To find out the role of pleural biopsy in the diagnosis of unilateral pleural effusion. Methods: This observational study was conducted in the Indoor patient department of Medicine in Rangpur Medical College Hospital from 01.01.2014 to 30.06.2014. All patients having unilateral pleural effusion above the age of 15 years irrespective of sex, race and religion was enrolled in this study. Results: Total fifty cases were enrolled in this study. Age of the patients varied from 16 to 78 years (Mean ±SD, yrs: 47±31.0). Thirty six (72%) patients were male and fourteen (28%) were female. 9 patients (18%) were of higher socio-economic status, 13 (26%) patients were from lower class, and 28 (56%) were from middle class. Majority (36%) of the patients were farmer, followed by 22% were businessman, 18% were service holder and 16% were housewives. Out of 50 patients, Nineteen patients (38%) were smoker and rests (62%) were non-smoker. Common presenting complaints were fever (78%), respiratory distress (62%), cough (56%), chest discomfort (38%) and weight loss (32%). General physical examination findings revealed 62% having different grades of anaemia followed by clubbing in 22% cases. Respiratory system examination revealed 56% having left sided pleural effusion followed by 44% right sided pleural effusion. 36% shows shifting of trachea. Regarding pleural fluid analysis, color of pleural fluid was straw in most cases (42%) and sixteen cases (32%) had hemorrhagic fluid. Mean total cell count in pleural fluid was 1449.1/c.mm. Most (88%) had lymphocyte predominance. Mean protein in pleural fluid was 5.6 gm/liter. Radiological examination revealed that maximum patient (56%) having left sided effusion and total 18 patients having shift of trachea. Close pleural biopsy for histopathological study revealed maximum (36%) were different types of malignancy, 24% chronic granulomatous inflammation consistent with tuberculosis, 16% shows non-specific chronic inflammation and 24% cases showed no abnormal findings or pleural tissue not available or inadequate tissue for histological report. Out of total 18 cases of malignancy, 08 revealed adenocarcinoma, 03 revealed metastatic adenocarcinoma, 02 revealed non-hodgkins lymphoma, 02 malignant mesothalioma and 03 of them revealed poorly differenciated carcinoma. Conclusion: In this study male are predominant. Most of the respondent was non-smoker. Most common presenting complains were fever, respiratory distress, cough, chest discomfort and weight loss. Most of general physical examination findings were anamia and clubbing. Respiratory system examination findings were features suggestive of pleural effusion (56% left sided and 44% right sided), 36% having shift of trachea. chest x-ray findings of most (56%) of the study population were left sided pleural effusion. Close pleural biopsy for histopathological study revealed maximum (36%) were different types of malignancy followed by chronic granulomatous inflammation consistent with tuberculosis (24%). Bangladesh J Medicine Jul 2016; 27(2) : 62-67